On the influence of finite initial deformations on the wave process in the system con sisting of an elastic half-space and a layer of a viscous compressible fluid - Bagno, A.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The problem of the propagation of acoustic waves in a previously deformed incompressible elastic half-space interacting with a layer of a viscous compressible fluid is considered. The study was carried out on the basis of three-dimensional linearized equations of the theory of elasticity of finite deformations for an incompressible elastic half-space and three-dimensional linearized Navier—Stokes equations for a layer of a viscous compressible fluid. The formulation of the problem and the approach based on the use of representations of general solutions of the linearized equations for an elastic body and fluid are used. A dispersion equation describing the propagation of harmonic waves in a hydroelastic system is obtained. Dispersion curves of surface waves are constructed in a wide frequency range. The effect of the finite initial deformations of the elastic half-space and the thickness of a layer of a viscous compressible fluid on the phase velocities, attenuation coefficients, and dispersion of surface waves in hydroelastic waveguides is analyzed. The numerical results are presented in the form of graphs, and their analysis is given.